Modulator-free approach towards missing-cluster defect formation in Zr-based UiO-66. Issue 47 (28th July 2020) - Chammingkwan, Patchanee; Shangkum, Goji Yildun; Mai, Le Thi Tuyet; Mohan, Priyank; Thakur, Ashutosh; Wada, Toru; Taniike, Toshiaki
Abstract : Missing-cluster defects in Zr-based UiO-66 can be generated by rigorous control of water without the need of acidic modulators. Abstract : By rigorous control of water, missing-cluster defects in Zr-based UiO-66 were generated to a remarkable extent without the need of acidic modulators. The presence of missing-cluster defects created hierarchical pore structures, which had a profound effect on the catalytic performance.